FACTORS INFLUENCING CORPORATE ETHICAL VALUES DISCLOSURES: A SYSTEMATIC LITERATURE REVIEW - Corina Joseph; Jennifer Tunga Janang; Sharifah Norzehan Syed Yusuf; Mariam Rahmat (International Journal of Business and Society, 2023)
The objective of this paper is to review the research patterns that examined factors influencing ethical values and practices disclosures among public listed companies in Malaysia. Through a systematic literature review (SLR) process, the paper reports a step-by-step approach to examining past studies and theories by utilizing the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) method. Past articles were identified through Scopus, Web of Sciences, and Google Scholar, which cover a period from when the Malaysian Code on Corporate Governance (MCCG) was established in 2000 until 2021. The results of our systematic literature review managed to categorize these factors into internal (board commitment, board characteristics, and company characteristics) and external (regulatory framework and international guidelines). While the sub-categories in each factor were mostly driven by compliance with the MCCG 2012 and MCCG 2017, the items on ethical practices and actions require more attention for further research. This paper recommends more studies to be conducted to examine these factors from the perspectives of board commitment, board characteristics, and firm characteristics as moderating variables. Our paper recommends large companies to adopt integrated reporting based on a globally recognised framework in promoting greater transparency and accountability as well as reducing duplication. The recommendations in this regulatory framework may influence the Board of Directors’ commitment to report more reflections of quality, and ethical values voluntarily. This paper is among the first of its kind to present a systematic literature review, which examines factors influencing ethical values and practices on disclosures, specifically in developing countries.